Nepal : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2007)
This report on the Observance of Standards and Codes on Fiscal Transparency of Nepal discusses fiscal transparency practices. Broad objectives of fiscal policy have been included in the budget speech, but the sustainability of fiscal policy over the longer term is not examined. Public reporting in relation to performance of the programs during budget implementation is weak. The government has undertaken a review of overall economic development and revised the estimates of revenue and expenditure. Internal control procedures are not fully effective, and the accounting system needs to be substantially strengthened.